Moulting behavior in leaf-frogs of the genus phyllomedusa (Anura : hylidae) - Castanho, L. M.; De Luca, IMS (Urban & Fischer Verlag, 2001)
The species belonging to the subfamily Phyllomedusinae presents physiological and behavioral adaptations to economise water such as secretion of lipids coupled with its spreading onto the skin surface through a complex behavior. adoption of diurnal torpor and secretion of uric acid. Here we describe other adaptation probably involved with water economy, registered in Phyllomedusa distincta, P. tarsius. P. tetraploidea and natural hybrids of P. distincta and P. tetraploidea - at dusk. these amphibians perform an elaborate moulting behavior that encompasses the cleaning of the body with the limbs plus gaping and body contractions. Our data show the daily moulting in P. distincta and suggest that the same mechanism occurs for the other species studied. We suppose that daily moulting improves the skin permeability to water being a characteristic of the phyllomedusines which spread lipids onto the skin surface.
Keywords: Amphibia; skin; water economy; brazil; Atlantic forest